Effect of Carrageenan Concentration on Sensory Characteristics of Jelly Drink Galoba - Gelora Helena Augustyn (Universitas Pattimura, 2022)
Galoba (Hornstedtia alliacea) is a fruit-producing plant belonging to the ginger-ginger tribe. Galoba has the potential to be processed into various processed products such as making jelly drinks. The manufacture of jelly drinks generally uses fruit extracts that have a high acidity level, such as galoba fruit, where the acidity level will affect the gel formed by the gelling agent. The gelling agent which is generally used for the manufacture of jelly drinks is carrageenan. The purpose of this study was to determine the appropriate concentration of carrageenan for the manufacture of jelly drink galoba. The research design used a one-factor completely randomized design with carrageenan concentration treatment consisting of 4 treatment levels, namely: K1: 0.10%, K2: 0.15%, K3: 0.20%, K4: 0.25%, each treatment repeated 3 times, so that the total experimental unit is 4 x 3 = 12 experimental units. Parameters of organoleptic properties were carried out by semi-trained analysts totaling 20 people using hedonik tests and hedonik quality which included color, taste, texture, suction power and overall. The results showed that the panelists' assessment of the color of the jelly drink of galoba fruit hedonik ranged from a scale value of 2.5 - 3.5 (slightly like to like), the hedonik quality ranged from a scale value of 2.5 - 3.2 (slightly cloudy white to cloudy white), the taste of jelly drink galoba fruit hedonik ranged from a scale value of 3.1 to 4.0 (like to really like), hedonik quality ranged from a scale value of 3.8 to 4 (close to somewhat tastes galoba to really taste galoba), jelly texture drink fruit galoba hedonik ranged from a scale value of 2.7 - 3.8 (close to somewhat like to somewhat like), hedonik quality ranged from a scale value of 2.1 to 3.4 (slightly chewy to chewy), jelly suction power drink fruit galoba hedonik ranged from a scale value of 3.1 – 3.7 (like to close to really like), the hedonik quality ranged from a scale value of 2.5 – 3.5 (somewhat easy to suck up to rather easy to suck).